Game On for Chemistry: How Kahoot Transforms Learning Outcomes and Student Interest - I. S. Al-Flayeh; Keziah C.B; Ruth Dikenwosi (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to determine the effect of Kahoot game media on students' interest and learning outcomes in chemistry lessons. Methodology: The method used is an experimental method with a quantitative approach to determine the level of interest and learning outcomes of students and to compare the level of interest and learning outcomes of students in the control class and the experimental class. Main Findings: The results of the t-test show a significance value of 0.000, then Sig. ˂ 0.05 so that there is an influence between the Kahoot game media and students' interest in learning. These results are supported by observation data with a significance value of 0.015, then Sig. ˂ 0.05. So it can be concluded that there is an influence between the Kahoot game media and students' interest in learning. The results of the Mann-Whitney test show a significance value of 0.749, then Sig. ˃ 0.05 so that it can be concluded that there is no significant influence between the use of Kahoot game media and students' learning outcomes. Novelty/Originality of this study: The novelty of this study lies in the use of Kahoot game media as an interactive approach to improve students' interest and learning outcomes in abstract and complex Chemistry lessons. This study is also relevant in the context of post-pandemic digital learning that demands technology-based innovation.